The FEM-prediction on Tensile Performance of Woven Membrane Materials under Uni and Bi-axial Loads (Journal of Fiber Bioengineering and Informatics, 2018)
In this study, the mechanical model of the woven PVC-coated membrane materials had been built. By the FEM analysis, it was found that when tensioned under uni-axial loads, the tensile modulus in the warp and fill direction of woven membrane materials was predicted satisfactorily, especially after the revision of properties of the fiber materials. The effect of the tensile moduli of the fiber and the PVC coating materials on the modulus of the woven membrane fabrics had been discussed. It was concluded that with the proper improvement of the modulus of the fiber materials in the fill direction, the discrepancy between the modulus of woven membrane materials in the warp and fill direction can be reduced to a certain extent. Considering prediction of modulus of the woven membrane materials under bi-axial loads, large difference was found between the predicted results and the experimental results, especially in warp direction. This was due to the fact that the mechanical analysis model reflected only the differences in geometric configuration between the warp and fill directions. However, the reinforcement of membrane materials in warp direction during weaving and coating processes had been ignored.
Keywords: FEM; membrane materials; coated fabrics; tensile modulus; uni-axial; bi-axial